2011
DOI: 10.1016/j.neulet.2010.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Oral methylphenidate establishes a conditioned place preference in rats

Abstract: Emerging data suggest that illicit methylphenidate abuse is a growing problem. Although abuse of the drug typically occurs by the intranasal route, oral (per os; p.o.) methylphenidate also has abuse potential. The present study compared the effects of p.o. and intraperitoneal (i.p.) methylphenidate in rats using the conditioned place preference (CPP) procedure. Young adult male Sprague-Dawley rats were trained to consume oyster crackers injected initially with saline. Next, rats were randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
4
5
0
Order By: Relevance
“…An important finding from the CPP studies is that the 1.25 mg/kg dose of MPH supported significant place preference, consistent with other recent reports investigating smaller doses of MPH (3 mg/kg or less) in the context of reward (dela Peña et al 2012; dela Peńa et al 2011; Trezza et al 2009; Wooters et al 2011). Interestingly, another recent report found that 0.75 mg/kg MPH did not support place preference in contrast to a 10-fold higher dose (Zhu et al 2011b), suggesting a lower limit to the reinforcing effects of MPH.…”
Section: Discussionsupporting
confidence: 89%
“…An important finding from the CPP studies is that the 1.25 mg/kg dose of MPH supported significant place preference, consistent with other recent reports investigating smaller doses of MPH (3 mg/kg or less) in the context of reward (dela Peña et al 2012; dela Peńa et al 2011; Trezza et al 2009; Wooters et al 2011). Interestingly, another recent report found that 0.75 mg/kg MPH did not support place preference in contrast to a 10-fold higher dose (Zhu et al 2011b), suggesting a lower limit to the reinforcing effects of MPH.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the decrease of the number of GluA1 subunits in the membrane, we also found a significant reduction of the AMPA-mediated EPSC and short-term plasticity in slices from rats treated repeatedly with MPH. A decrease in the AMPA-mediated EPSC has also been observed in NAc slices prepared from young mice treated for 5 days with cocaine (Wooters et al, 2011). This reduction is consistent with previous evidence showing that repeated amphetamine administration decreases the levels of GluA1 and GluA2 mRNA in NAc at day 14 of withdrawal time (Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…dose; CPP to MPH was blocked by the general dopamine antagonist cis-flupenthixol. Wooters et al [14] showed that intraperitoneal administration of 3 or 10 mg/kg MPH produced CPP, but only a high dose of orally administered MPH (10 mg/kg) produced CPP. Interestingly, there are only two studies which have analyzed MPH CPP in adolescent animals.…”
Section: Introductionmentioning
confidence: 99%